SOSIALISASI PENCEGAHAN DAN PENANGANAN KEBAKARAN KOMPOR DI DESA SUMBER RT 07 RW 01, KECAMATAN SUKOREJO, KABUPATEN KENDAL - Mugni AlGhifari, Muhammad; Imam Muslim, Rachmat; Bagus Primadoni, Ade; Faida, Mar'atul; Kusumawati, Dian; Tri Wuryani, Meylan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Fires are a common disaster that can cause significant damage. Most fires are caused by negligence, such as failure to inspect gas stove hoses and unsupervised risky activities. Additionally, the public’s lack of knowledge and awareness regarding fire prevention and initial response poses a major challenge. Therefore, this activity aims to enhance the public’s knowledge and preparedness in preventing and managing stove fires in Sumber Village, RT 07/RW 01, Sukorejo Subdistrict. This activity also aims to provide education on the causes and risks of fires, improve understanding of preventive measures, train participants in simple initial fire response, and foster public awareness of the importance of safety regarding fire risks. This activity employed educational and participatory methods through lectures, demonstrations, and interactive discussions, supplemented by evaluations to measure improvements in community understanding. The results of the activity demonstrated increased knowledge, participation, and community awareness regarding fire prevention and initial fire response; thus, it can be concluded that the activity was successfully implemented and received a positive response from the community.